Nanostructured superhydrophobic films synthesized by electrodeposition of fluorinated polyindoles - Ramos Chagas, Gabriela; Darmanin, Thierry; Guittard, Frédéric (Beilstein Journal of Nanotechnology, 2015)
Materials with bioinspired superhydrophobic properties are highly desirable for many potential applications. Here, nine novel monomers derived from indole are synthesized to obtain these properties by electropolymerization. These monomers differ by the length (C4F9, C6F13 and C8F17) and the position (4-, 5- and 6-position of indole) of the perfluorinated substituent. Polymeric films were obtained with C4F9 and C6F13 chains and differences in the surface morphology depend especially on the substituent position. The polyindoles exhibited hydrophobic and superhydrophobic properties even with a very low roughness. The best results are obtained with PIndole-6-F6 for which superhydrophobic and highly oleophobic properties are obtained due to the presence of spherical nanoparticles and low surface energy compounds.
Keywords: bioinspiration; conducting polymers; electrochemistry; nanostructures; polyindoles; superhydrophobic